Determination by response surface methodology of optimal protein and phycocyanin productivity conditions in Arthrospira (Spirulina) platensis under different combinations of photoperiod variation and lighting intensity. (September 2021) - Junique, Laura; Watier, Lucie; Lejeune, Hortense; Viudes, Florence; Deblieck, Marie; Watier, Denis
Abstract: The objective of this study is to determine the lighting conditions for an optimal production of Arthrospira ( Spirulina ) platensis quantitatively and qualitatively for the process most commonly used by producers. A design of experiments made it possible to obtain surface modelling of responses which were validated under pilot conditions. Spirulina growth, protein and pigment content were modelled as a function of light intensity and duration of illumination. For each of them, the optima have been determined: 14 h (hours light exposure)/10 Klux (light intensity) for the growth rate; 11.8 h/7.2 Klux for phycocyanin rate; 6.2Klux/12.6 h for chlorophyll rate; 6.6Klux/12.6 h for carotene rate. The protein rate is the lowest when lighting conditions are of 10.6 Klux and 14.4 h. It is then possible for the producer to partially obscure the ponds and/or increase the light intensity using additional lighting. Graphical abstract: Unlabelled Image Highlights: Productivities in biomass, proteins and pigments were differentially influenced by the lighting Spirulina production requires compromises in the quantitative and qualitative aspect The protein level in spirulina is favored by slow growth